Communicating Across Eternal Divides: Conceptualizing Communicated Acceptance During Parent-Child Religious Difference. Issue 4 (2nd October 2022) - Morgan, Toni; Kellas, Jody Koenig
ABSTRACT: Significant religious difference in the family has become increasingly prevalent in recent years. While religious difference may be challenging for families to negotiate, the manner in which family members communicate about it seems to be helpful in promoting positive interactions between parents and children. The purpose of this study was to conceptualize a parental communicated (non)acceptance continuum in the context of significant parent-child religious difference. We conducted semi-structured interviews with 44 adults who identified a significant religious difference with their parent. The results suggested that communicated (non)acceptance occurred along a continuum with four ranges of behaviors: communicated nonacceptance, ambivalence, communicated acceptance, and idealized communicated acceptance. We discuss the characteristics of each part of the continuum and conclude by identifying key theoretical and translational implications.